Analysis of Political Economiy Power to Access Land Forest (The Case of Three Communities in Production Forest Tebo District Jambi) - Nurul Hidayati, Hilda; Hadi Dharmawan, Arya; K. Pandjaitan, Nurmala (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTThe overlapping of forest management in Indonesia is one of explaining factor in people to occupy forest land. In Jambi, it was identified three communities which grab forest land in production forest area in which many of this area is concessioned to PT. ABT due to ecosystem restoration since 2015. Three communities living in those area are Talang Mamak, Malay Suo-Suo, and migrant from outside region. From this situation, there is a problem relating to the uncertainty of occupation area by three communities in which it is identified inside forest consession area or outside forest consession area of PT. ABT. The other critical issues is that until recently these three community are still able to encroach illegal land and grab the land. It is then questioned what power that three community have, to support their action in encroaching the land. Therefore, focus of this research is to analyze power of three communities to occupy forest land. Power analysis was performed by identifying bundle of power through the mechanism of access by three communities. This research used a qualitative and quantitative research. Data collection technique used in-depth interview, observation, structural interview, and literature study. The results showed that there are three powers that be the strength of the community that is political power, ideological power, and connections power.Keywords: Power, access, production forestABSTRAKPengelolaan hutan yang tumpang tindih di Indonesia menjadi faktor penyebab bagi masyarakat untuk mengokupasi lahan hutan. Di Jambi, teridentifikasi tiga komunitas mengokupasi lahan hutan di kawasan hutan produksi yang sebagian wilayahnya dikonsesikan kepada PT. Alam Bukit Tigapuluh sejak tahun (ABT) 2015 untuk restorasi ekosistem. Tiga komunitas tersebut antara lain Suku Talang Mamak, Orang Melayu Suo-suo, dan pendatang. Dari situasi ini, ada sebuah persoalan berkaitan dengan ketidakjelasan area okupasi apakah area yang diokupasi oleh tiga komunitas tersebut teridentifikasi ke dalam area hutan konsesi PT. Alam Bukit Tigapuluh atau di luar area hutan konsesi. Isu penting lainnya adalah bahwa sampai saat ini tiga komunitas ini masih mampu melanggar batas tanah ilegal dan mengambil tanah tersebut. Hal ini menimbulkan pertanyaan kekuasaan apayang dimiliki oleh tiga komunitas, untuk mendukung aksi mereka di dalam kawasan okupasi. Oleh karena itu, fokus penelitian ini adalah untuk menganalisis kekuatan tiga komunitas untuk mengokupasi lahan hutan. Analisis kekuasaan dilakukan dengan mengidentifikasi bundle of powermelalui mekanisme akses oleh tiga komunitas. Penelitian ini menggunakan pendekatan kualitatif dan kuantitatif. Teknik pengumpulan data yang digunakan wawancara mendalam, observasi, wawancara struktural, dan studi literatur. Hasil penelitian menunjukkan bahwa ada tiga kekuasaan yang menjadi kekuatan komunitas yaitu kekuasaan politik, kekuasaan ideologi, dan kekuasaan relasi.Kata kunci: Kekuasaan, akses, hutan produksi